The Role of Culture in Business Sustainability in Resource Based Theory: A Comprehensive Review - Kadek Wulandari Laksmi P; Ida Bagus Anom Purbawangsa; I Gde Kajeng Baskara; Luh Gede Sri Artini (Jurnal Ilmu Sosial dan Humaniora, 2024)
Sustainability has become a critical concern for businesses across the globe, driven by a range of stakeholder demands and the need to address pressing environmental and social challenges. While the focus on sustainability is important, it is crucial to consider the potential drawbacks of prioritizing culture in business sustainability within the context of resource-based theory. Some argue that overly emphasizing culture in sustainability efforts can lead to a lack of focus on other important factors, such as technological innovation and economic considerations. This paper aims to explore the impact of organizational culture on sustainable business practices and competitive advantage and develop a framework for aligning them to drive long-term success. The approach includes conducting a systematic literature review using the Scopus database. The results are a comprehensive analysis of the role of organizational culture in sustainable business practices and the implications for resource-based theory. In conclusion, organizational culture plays a significant role in sustainable business practices and can contribute to competitive advantage. Future research must explore how to balance cultural factors with other strategic considerations. Additionally, the study emphasizes the importance of inclusive leadership and diversity management in fostering a culture of inclusivity and belonging, which is crucial for sustainable development and long-term organizational success.